Holomorphic Distributions and Connectivity by Integral Curves of Distributions - Zorich, V.A. (Symmetry, Integrability and Geometry: Methods and Applications, 2019)
It is known that the classical Frobenius theorem on conditions of integrability for distributions of planes can be extended to the case of complex holomorphic distributions. We show that an alternative criterion for integrability, namely, non-connectivity, discovered (or at least, marked and explicitly formulated) by Carathéodory in relation to classical thermodynamics, also admits a holomorphic formulation.